Hubungan Tinggi Badan Ibu dengan Stunting pada Balita di Kecamatan Peurlak, Kabupaten Aceh Timur - Maisyura Maisyura; Intan Nuraini Harahap; Nura Farika Jefri; Sri Jayanti (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Stunting (short toddlers) in Indonesia is a nutritional problem that is still a priority, this is because nutritional problems have an impact on the quality of human resources (HR). The prevalence of stunting from the 2013 Basic Health Research was 37.2%, while the results of recording nutritional status in 2016 were 27.5%, much higher than the WHO limit of <20%. Objective: To determine the relationship between maternal height and stunting under five children in Peureulak, East Aceh. Method: This type of research is analytic observational with a case-control study design that was traced retrospectively, statistical test using chi square. Results: Based on the results of the bivariate chi square analysis in table 2, it is known that the height of the mother is at higher risk in the case group of toddlers (stunting) as many as 58 people compared to the control group (not stunting) which is 16 people. P value of 0.0005 with an odds ratio of 2.9. Conclusion: There is a relationship between maternal height and the incidence of stunting in children aged 0-59 months in Peureulak District, East Aceh District.